2010
DOI: 10.1371/journal.pntd.0000732
|View full text |Cite
|
Sign up to set email alerts
|

Serological Studies of Neurologic Helminthic Infections in Rural Areas of Southwest Cameroon: Toxocariasis, Cysticercosis and Paragonimiasis

Abstract: BackgroundBoth epilepsy and paragonimiasis had been known to be endemic in Southwest Cameroon. A total of 188 people (168 and 20 with and without symptoms confirmed by clinicians, respectively, 84.6% under 20 years old) were selected on a voluntary basis. Among 14 people (8.3%) with history of epilepsy, only one suffered from paragonimiasis. Therefore, we challenged to check antibody responses to highly specific diagnostic recombinant antigens for two other helminthic diseases, cysticercosis and toxocariasis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…In addition, people outside of Asia may also suffer from this disease [18]. The World Health Organization(WHO) estimates that about 20.7 million people are suffering from paragonimiasis [1].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, people outside of Asia may also suffer from this disease [18]. The World Health Organization(WHO) estimates that about 20.7 million people are suffering from paragonimiasis [1].…”
Section: Discussionmentioning
confidence: 99%
“…The 35 kDa protein spotted into protein chip could be used for the diagnosis of paragonimiasis, although further verification is needed to investigate if the protein is the same as the 35 kDa in P. westermani adult worm soluble antigens [63]. Moreover, it has been reported that the specificities using well-archived serum samples of sera-diagnosis for detection of different FBHs are ideal with positive percentages ranging from 83% to 100%, while the sensitivities ranged from 50 to 98% [16]–[18], [21], [28], [29], [64], [65]. In spite of the semi-purified proteins prepared for each parasites in the study, such as the 95 kDa protein of C. cellulosae , the 98 kDa protein of A. cantonensis , the 35 kDa protein of P. westermani , the 55 kDa protein of T. spiralis and the 90 kDa protein of Spirometra spp.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoassays for antibody and molecular detection have proven useful for epidemiological studies of FBHs for a long time [16]–[18], [21], [28], [29], [31], [32]. However, each of these methods and techniques has limitations in that they could not detect multiple parasitic infections by the application of just one test.…”
Section: Introductionmentioning
confidence: 99%
“…Central nervous system infectious pathogens with epilepsyrelated sequelae are more common in developing countries and include bacterial meningitis and viral encephalitides, such as Japanese encephalitis [14], dengue [15], and chikungunya [16]. Common tropical pathogens with associated postinfectious seizure disorders include tuberculosis, HIV, toxocariasis [17], paragonimiasis [17] and schistosomiasis [18,19]. Neurocysticercosis continues to contribute substantially to the global burden of epilepsy [20][21][22].…”
Section: Key Pointsmentioning
confidence: 99%